Effects of Environmental Factors on the Temporal Stability of Phytoplankton Biomass in a Eutrophic Man-Made Lake - Wang Tian (Water, 2016)
The stability of phytoplankton biomass is important in maintaining the health of an aquatic ecosystem. In this study, the main environmental factors and phytoplankton biomass were investigated monthly from May 2011 to April 2013 in a eutrophic lake. The influence of both the mean values and variability (standard deviation) of environmental factors on the temporal stability index (TSI, measured as coefficient of variation) of phytoplankton was analyzed. Complex relationships were observed between the mean environmental factors and phytoplankton TSI: a positive relationship for dissolved oxygen (DO) and pH, a negative relationship for total nitrogen (TN) and ammonia nitrogen (NH4+-N), a unimodal relationship for total phosphorus (TP), and no relationship for water temperature (WT). Mean values of DO and pH mainly influenced the stability of phytoplankton through increasing the average total biomass. However, mean TN and NH4+-N concentrations destabilized phytoplankton TSI primarily through increasing the variability of community biomass. There were also complex relationships between the variability of environmental factors and phytoplankton TSI: a negative relationship for TN, a unimodal relationship for NH4+-N and TP, and no relationship for WT, DO, and pH. The variability of nutrient concentrations mainly affected phytoplankton TSI through influencing the variability of community biomass, while their influence on the average total biomass was weak. Results in this research will be helpful in understanding the influence of environmental factors on the temporal stability of phytoplankton.